PRELIMINARY STUDY OF RETROVIRAL MEDIATED TRANSFER OF THE HUMAN mdr-1 GENE INTO MURINE AND HUMAN HEMATOPOIETIC STEM/PROGENITOR CELLS - Feng, Kai; Pei, Xuetao; Wang, Lisheng; Gao, Wenqian; Xu, Li; Wang, Yuzhi; Li, Liang; Wu, Chutse (Chinese Journal of Cancer Research, 2013)
To investigate the characteristics of multidrugresistance and transplantation of modified stem/ progenitor cells by multidrug-resistant gene (mdr-1 gene), we established PA317/MDR-1 cell line which producing retroviruses by transfecting the retroviral vector PHaMDRI/A into packging cell line PA317 by Lipofectin. The virus titer of the supernatants was 1.2 xl05 cfu/ml. We transfected the murine hematopietic cells collected from 5-FU pretreated mice and they showed the ability to reconstitute the long-term hematopoiesis of pre-irradiated mice. After 4 months, both of bone marrow ceils and peripheral blood cells of transplanted mice still contained mdr-1 gene. We also transfered mdr-1 gene into human bone marrow CD34+ cells selected by using magnetic cell sorting system. PCR analysis showed that transduced CD34+ cells maintained the mdr-1 cDNA. A fraction of CFU-GM originated from transfected CD34+ cells had the charactor of resistance to Taxoi. It is indicated that mdr-I gene can be transduced into murine and human stem/proginitor cells through retroviral mediated gene transfer and it protects the transfected cells from cytotoxic drugs.